Вдосконалення професійної підготовки майбутніх вихователів дошкільних закладів освіти у процесі педагогічної практики - Чичук Антоніна; Chychuk Antonina; Csicsuk Antonina; Біда Олена; Bida Olena; Гуттерер Єва; Hutterer Éva (Видавництво «Код», 2025)
Резюме. Метою статті є вдосконалення підготовки майбутніх вихователів дошкільних закладів освіти у процесі педагогічної практики. На основі проведеного аналізу літератури з’ясовано мету і завдання педагогічної практики.

Abstract. The purpose of the article is to improve the training of future teachers of preschool educational institutions in the process of pedagogical practice. Based on the analysis of the literature, the purpose and objectives of pedagogical practice are clarified. The features of a new approach to the organization of pedagogical practice are revealed, which is formed on the following principles: the key tasks of pedagogical practice are to develop individual pedagogical abilities of students; pedagogical practice is an integrated part of all theoretical training programs in a higher educational institution and, first of all, the disciplines of the psychological and pedagogical cycle. Such a combination of theory and practice ensures a comprehensive correlation of theoretical knowledge with pedagogical activity. Pedagogical practice helps to eliminate the barrier between the theory and practice of teacher training, to develop students’ independent activity and to ensure their creative activity. The features of pedagogical practice in Great Britain are revealed - two approaches to its implementation: block practice and serial practice. In the process of continuous pedagogical practice, the professional development and self-determination of future teachers are intensified, their theoretical knowledge is updated and deepened, and the formation of pedagogical skills, abilities and qualities of the teacher’s personality is accelerated. Pedagogical practice helps to develop the student and ensure their creative activity. It is proved that the emergence of creativity in preschool age is determined both by the features of preschoolers’ mastery of the content of the activity itself, and by the features of relationships with the environment and depends on the training of future teachers of preschool educational institutions. The driving force behind the refusal to imitate the actions of an adult and the transition to the conscious inclusion of inventions in activity is the possibility of satisfying the need for recognition by means of inventive and creative imitation. Parents and educators should help develop the creative abilities of preschoolers. Therefore, improving the training of future educators of preschool educational institutions in the process of pedagogical practice is an important task of our time.
Improvement of future teachers professional training of preschool educational institutions in the process of pedagogical practice
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00015728 Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-11
Keywords: професійна підготовка; майбутні вихователі; заклади дошкільної освіти; педагогічна практика; розвиток творчих здібностей дошкільників